« Nous sommes d’accord sur presque tout » ; l’impossible compromis ? - Monique Vénuat (Caliban: French Journal of English Studies)
This paper addresses the controversy between Thomas Cranmer, Archbishop of Canterbury (1489-1556), and Stephen Gardiner (c. 1497-1555), late bishop of Winchester, in 1550 and 1551, in the context of the revision of the first English Book of Common Prayer during the reign of Edward VI. It focuses on the occasional instances in which Cranmer, or less frequently Gardiner, agrees “almost in everything” with his opponent in the theological conflict; it attempts to determine whether such statements imply irony and the awareness that the breach between Catholic and Protestant tenets on the Eucharist is unbridgeable, or whether they point at the hope of reaching a comprehensive settlement.